PERFORMANCE OF BASE ISOLATION APPLICATION IN MULTISTORY BUILDING - Winda
Indonesia is a country that has huge potential of earthquakes. Therefore, earthquake resistant building is needed in infrastructure development. Some structures, for example hospitals and important government buildings, are expected to have immediate occupancy performance. Immediate occupancy is a condition in which a building still can be operated right after the earthquake. For achieving this performance, without using excessive profile, it is needed to apply damper technology in structure. Base isolation is one of the examples of passive damper, which can reduce earthquake force that is suffered by the structure. The principal work of base isolation is to separate the structure from the ground, thus the input force from the earthquake is reduced. This final project discusses the effect of application of lead rubber bearing in three steel structures; each of them is 3, 10, and 20 stories. The methods conducted in this final project are started with preliminary design of structure’s profile by applying gravitational and earthquake load. Then, in these three structures, design of base isolation will be conducted to their possible optimum state. After application of isolator in each building, the change in structure’s behavior will be observed. Parameters that will be observed are base shear, story shear, roof displacement, inter-story drift, and internal force. From calculation result and analysis, It can be concluded that application of base isolation will reduce base shear, reduce relative roof displacement, and increase structure’s first mode. Moreover, in comparison among the building with base isolation, application of base isolation in 3 stories building is more effective than other buildings.